Assistance in Creating Nutrition Fact Labels and Packaging for Cassava Chips Products at CV. Eka Pratama Sejahtera Cirebon - Khoiriyah, Nur; Fazdilah, Ayu Cindy; Hartati, Wiwi; Maharani, Puja (Edumedia Solution, 2025)
Micro, small, and medium enterprises (MSMEs) frequently encounter numerous challenges, including the incorporation of nutrition fact labels and product packaging—this community service aimed to facilitate the creation of nutrition fact labels and new packaging for MSME products. The partner of this program was CV Eka Pratama Sejahtera in Cirebon Regency, focusing on cassava chip products. This program included observation, problem identification, activity implementation, and evaluation. Observations and problem identification indicated a necessity for new flavor varieties, nutritional fact labels, and updated packaging for cassava chip products. The results showed that CV Eka Pratama Sejahtera provided positive feedback during this assistance program. This program successfully generated a nutrition facts table for a new flavor variant of cassava chips using the BPOM format. Additionally, this program developed a new packaging design for the product. The result of this program was the redesigned packaging, which included nutritional information for the latest flavor variants of cassava chip products at CV Eka Pratama Sejahtera.